Comida, comensalidade e reclusão. Sentidos do que se (não) come, como e com quem numa prisão portuguesa - Cunha, Manuela Ivone (Trabalhos de Antropologia e Etnologia, 2020)
The “social fact” of food is considered in this paper as an object in itself, in the specific characteristics that it assumes in a prison context and, at the same time, as a window onto the prisoners social and moral world. The particular meanings that food is endowed with in prison are connected with institutional power, with the identities it puts to the test or that resist it, with the cut it establishes with the outer world or with the continuity with that same world that prisoners seek to preserve. However, the meaning of other lesser-known aspects concerning the relation between commensality and prison sociality can only be fully grasped through the comparison of different forms. Drawing from an ethnography in a Portuguese prison, I will focus on two periods in which opposite configurations prevailed. These were contrasting empirical realities whose relevance was then first and foremost descriptive. Today they can also be understood as ideal-types with analytical relevance, even when their empirical expression is more mitigated. What the comparison between such configurations shows is that the meaning of food and commensality is shaped not only by the "carceral" character of the context in question, but also by the "contextual" character of the social relations that take place in prison.